2022
DOI: 10.7759/cureus.29496
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Vitamin D and Basal Cell Carcinoma: A Systematic Review

Abstract: This systematic review studies the relationship between vitamin D serum levels and basal cell carcinoma (BCC). The primary source of vitamin D is sunlight exposure. Recently, an increase in the intake of vitamin D supplements has been noticed. The protective value of vitamin D is well established and has been studied several times for the health of the bones, cartilage, growth, various dermatological diseases, and also as a chemoprotective agent against several cancers. On the scientific front, it has yet to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Our literature search yielded a total of 269 relevant articles. Ten SRs fulfilled our eligibility criteria and were included in the review, with 7 of those conducting meta-analysis of the data [13,14,[22][23][24][25][26][27][28][29]. The study selection process is depicted by the flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our literature search yielded a total of 269 relevant articles. Ten SRs fulfilled our eligibility criteria and were included in the review, with 7 of those conducting meta-analysis of the data [13,14,[22][23][24][25][26][27][28][29]. The study selection process is depicted by the flow diagram (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two examined the chemoprotective role of VitD on BCC and SCC, with Sutedja et al testing its role in patients with confirmed malignancies [27]. Of note, Abdelwahab et al included 4 studies from Mahamat-Saleh et al in their review [22]. Overall, 4 RCTs were included in 4 out of the total 10 SRs, included in the overview, as portrayed in the citation matrix (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The debate also extends to the therapeutic strategy option of Vitamin D supplementation in patients with BCC. Although meta-analysis has evinced a protective effect of lower vitamin D levels regarding BCC occurrence, there are studies supporting the proposition that higher levels of vitamin D are associated with higher risk of BCC, making the relationship between skin cancer and vitamin D more unclear [13]. A study that focused on the role of vitamin D receptor (VDR) polymorphisms in non-melanoma skin cancer development is also worth mentioning, since it reported a possible relationship between the two [14], highlighting the role of vitamin D in skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Second, melanoma and non-melanoma lesions have a significant relationship. The environment, which includes hair, veins, and illumination, is the third factor ( 8 ). When the number of images required to train a deep convolutional neural network (DCNN) is insufficient, conventional augmentation is widely used.…”
Section: Introductionmentioning
confidence: 99%